2018
DOI: 10.3389/fendo.2018.00649
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives on GLP-1 Receptor Agonists and GLP-1/glucagon Receptor Co-agonists in the Treatment of NAFLD

Abstract: Along the obesity pandemic, the prevalence of non-alcoholic fatty liver disease (NAFLD), often regarded as the hepatic manifestation of the metabolic syndrome, increases worldwide representing now the prevalent liver disease in western countries. No pharmacotherapy is approved for the treatment of NAFLD and, currently, the cornerstone treatment is lifestyle modifications focusing on bodyweight loss, notoriously difficult to obtain and even more difficult to maintain. Thus, novel therapeutic approaches are high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 82 publications
0
56
0
3
Order By: Relevance
“…Liraglutide, an antidiabetic GLP-1 agonist, in a phase 2 clinical trial, resulted in histological resolution of NASH in 39% of patients, compared with only 9% of patients treated with placebo [35]. More recent studies, in several different countries, have found similar results [36][37][38][39]. Pioglitazone, a PPARγ agonist, improved NASH histology both in patients with prediabetics and with type 2 diabetes, with a greater improvement in fibrosis in those with type 2 diabetes [40], and is endorsed by multiple international societies for the treatment of patients with NAFLD [41][42][43][44].…”
Section: Prevention Of Nafld/nash Associated Primary Liver Cancermentioning
confidence: 84%
See 1 more Smart Citation
“…Liraglutide, an antidiabetic GLP-1 agonist, in a phase 2 clinical trial, resulted in histological resolution of NASH in 39% of patients, compared with only 9% of patients treated with placebo [35]. More recent studies, in several different countries, have found similar results [36][37][38][39]. Pioglitazone, a PPARγ agonist, improved NASH histology both in patients with prediabetics and with type 2 diabetes, with a greater improvement in fibrosis in those with type 2 diabetes [40], and is endorsed by multiple international societies for the treatment of patients with NAFLD [41][42][43][44].…”
Section: Prevention Of Nafld/nash Associated Primary Liver Cancermentioning
confidence: 84%
“…The molecular underpinnings of the evolution from NAFLD to NASH to liver cancer (with or without cirrhosis) are well understood [5,19,52], and multiple studies are underway targeting specific parts of this progression [30,[36][37][38][39]53]. NAFLD and NASH typically occur in patients with metabolic syndrome.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The pathophysiology of NAFLD includes (apart from dietary fat contribution) proinflammatory cytokines, hepatic and adipose tissue insulin resistance, lipotoxicity, and oxidative stress. A reduced hepatic glucagon resistance, together with an impaired incretin effect, may be additional mechanisms [53]. Although the functional receptor for GIP (GIPR) was not found in the liver, this incretin hormone may play a role in hepatic steatosis exerting pleiotropic effects in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…20 % aggraviert die Fettlebererkrankung zu einer Steatohepatitis (NASH), die durch eine vermehrte Produk-tionreaktiverSauerstoffspezies(ROS)mitErhöhungpro-inflammatorischerZytokinesowieverminderterVerfügbarkeit antiinflammatorischer Adipokine bedingt wird [38]. Eine Therapie mit GLP-1-Rezeptoragonisten könnte diesen pathophysiologischen Teufelskreis auf verschiedene Arten durchbrechen (Gewichtsabnahme durch zentrale Regulation der Nahrungsaufnahme, Reduktion der Lipogenese und der freien Fettsäuren, Erhöhung der Insulinsensitivität,ReduktionproinflammatorischerZytokine, Erhöhung des Adiponektin/Leptin-Verhältnisses) [38]. Erste vielversprechende Daten zeigen, dass Liraglutid vs.…”
Section: Effekteaufdienichtalkoholische Fettlebererkrankungunclassified
“…Placebo eine deutliche histologische Remission der NASH (39%vs.9%,p=0,019)bewirkenkann [39].WeitereStudien zu Semaglutid und Dualen-Agonisten (wie beispielsweise GLP-1/GIPR oder GLP-1/GCGR-Co-Agonisten) wurden initiiert bzw. sind in Vorbereitung [38].…”
Section: Effekteaufdienichtalkoholische Fettlebererkrankungunclassified